(untitled) (Journal of Kidney Cancer, 2021)
Obesity has been established as a risk factor for renal cell carcinoma (RCC). Recently, studies have described obesity as a probable protecting factor in the metastatic stage of RCC. In this study, we assessed the relationship between body mass index (BMI) and overall survival in patients under systemic therapy. The correlation between BMI and overall median survival was studied in 76 patients diagnosed with metastatic RCC under systemic therapy. The groups were divided into overweight and obesity (BMI > 25 kg/m2) and underweight or normal (BMI < 25 kg/m2). Statistical analysis was performed using the Cox regression model adjusted by gender. A total of 76 patients were studied: 16 women (21%) and 60 men (79%). The median BMI was 27.96 kg/m2; 24 patients (31.6%) had low BMI and 52 (68.4%) had high BMI. Median overall survival in the group with BMI > 25 kg/m2 was 17 months (95% confidence interval [CI]: 13–34 months), while in the group with BMI ≤ 25 kg/m2, it was 14 months (95% CI: 8–20 months). When adjusted by gender, the group with BMI > 25 kg/m2 presented a hazards ratio of 0.54 (95% CI: 0.30–0.96), P = 0.044 (Log Rank). A high BMI significantly acts as a protecting factor. We observed an increased overall survival of overweight and obese patients within the context of metastatic RCC under systemic treatment. These data confirm the findings published in other studies that suggest the role of lipid metabolism in this type of tumors.